Development and Validation of a Problem-Based Learning (PBL)-Based Science Worksheet on Environmental Pollution for Grade VII Junior High School Students - Yansah, Edi; Yokos Pranata; Nurlia Latipah (Yayasan Darussalam Bengkulu, 2024)
This study aims to develop and validate a PBL-based science worksheet on environmental pollution for Grade VII students in Indonesian junior high schools. The worksheet was designed using the Borg and Gall development model, adapted by Sugiyono, and was validated by experts in content, language, and design. The validation process resulted in positive assessments, with content and language experts rating the worksheet at 80%, indicating its alignment with curriculum goals and appropriateness for the target grade. Media and design validation was rated at 70.58%, suggesting room for improvement in visual appeal. The worksheet was then field-tested with 10 students and one teacher, receiving high practical ratings of 88.3% from students and 96.19% from the teacher, indicating its effectiveness in fostering student engagement and learning. The findings suggest that PBL-based worksheets can enhance critical thinking, environmental awareness, and problem-solving skills, supporting the development of more interactive and student-centered learning environments. Despite some design-related limitations, the study highlights the potential of PBL as an effective teaching strategy for promoting active learning in science education. Future research should explore the broader applicability of PBL-based tools across different subjects and educational settings.